PENGARUH BAURAN PEMASARAN DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN PELANGGAN HOME INDUSTRI BAGINDA LAMPION DI KABUPATEN WAKATOBI. - Raifudin Raifudin; Patwayati Patwayati; Noval Nur (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to: 1) analyze the effect of marketing mix and product innovation on purchasing decisions 2) analyze the effect of marketing mix, product innovation and purchasing decisions on customer satisfaction. 3) analyze the effect of marketing mix on customer satisfaction mediated by purchasing decisions. 4) analyze the effect of product innovation on customer satisfaction mediated by purchasing decisions. The research population is the Home Industry Consumer of His Majesty Lampion, totaling 105 respondents, the technique of determining the sample is using the census technique so that the number of research samples is 105 respondents. Methods of data collection using a questionnaire. The research data was processed using the smart PLS 2 application to test the direct and indirect effects. The results of the study: 1) marketing mix and product innovation have a positive and significant effect on purchasing decisions, 2) marketing mix and product innovation have a positive but not significant effect on customer satisfaction, while purchasing decisions have a positive and significant effect on customer satisfaction, 3) marketing mix has an effect positive and significant impact on customer satisfaction mediated by purchasing decisions, 7) product innovation positive and significant effect on customer satisfaction mediated by purchasing decisions.